2009
DOI: 10.1016/j.jfoodeng.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Application of turbulent pulsating flows to the bacterial removal during a cleaning in place procedure. Part 2: Effects on cleaning efficiency

Abstract: Pulsating turbulent flows effects on cleaning in place procedure of straight pipes were investigated for various pulsations parameters (frequency and amplitude) and mean velocities of the flow. Pulsations generation was made with a new system which allows high amplitude of pulsations. Experiments showed the contribution of the different pulsation parameters, in the removal of adhered bacterial spores, in addition to the effect of the mean velocity of the flow. A high level of the cleaning rate is observed desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Some previous works suggest advantages of applying different CIP procedures such as pulsing cleaning chemicals (Christian and Fryer, 2006) or pulsed flows (Blel et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Some previous works suggest advantages of applying different CIP procedures such as pulsing cleaning chemicals (Christian and Fryer, 2006) or pulsed flows (Blel et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pulsating and oscillatory flows provide for rapidly changing shear stresses on the membrane surface, which contribute to the prevention of fouling and thus assist the filtration process. At the same time, transient flows exert lift and drag forces on the particles and facilitate the migration of particles from the membrane surface to the bulk flow . For example, the filtration performance of yeast cell harvesting was greatly improved by using oscillatory flow mixing in both tubular and flat‐sheet membrane systems .…”
Section: Introductionmentioning
confidence: 99%
“…A potential approach is the utilization of pulsatile jets. It had already been shown that a change from continuous to pulsed cleaning results in higher cleaning rates in pipes or surfaces from particles or other types of fouling . The filtration performance of membranes or filter cloths, in particular, is enhanced by using pulsatile flows, which are in some cases even more effective than cross‐flows , , .…”
Section: Introductionmentioning
confidence: 99%